The impacts of heat stress on animal cognition: Implications for adaptation to a changing climate. (27th April 2021) - Soravia, Camilla; Ashton, Benjamin J.; Thornton, Alex; Ridley, Amanda R.
Abstract: With global surface air temperature rising rapidly, extensive research effort has been dedicated to assessing the consequences of this change for wildlife. While impacts on the phenology, distribution, and demography of wild animal populations are well documented, the impact of increasing temperature on cognition in these populations has received relatively little attention. Cognition encompasses the mental mechanisms that allow individuals to process information from the surrounding environment, respond accordingly, and flexibly adjust behavior. Hence, it is likely to be a key factor in allowing animals to adjust adaptively to climate change. Captive studies show that heat stress can negatively affect cognitive performance not only in the short‐term but also in the long‐term, by altering cognitive development at early life stages. Field studies indicate that cognitive performance may affect survival and reproductive success. However, the link between heat stress, cognition, and fitness in wild animals has yet to be formally established. We propose a comprehensive research framework for the collection of robust empirical datasets on heat stress and cognitive performance in the wild. We then suggest how knowledge of heat stress impacts on cognitive performance could be applied to population viability models and wildlife management actions. We believe that a joint research effort encompassing the fields of thermal physiology, behavioral ecology, comparative cognition, and conservation science, is essential to provide timely mitigation measures against the potential impacts of climate change on wildlife. This article is categorized under: Climate, Ecology, and Conservation > Observed Ecological Changes Abstract : Does increasing temperature alter cognition, that is, an animal's ability to acquire, process and act on environmental information? The question is crucial because cognition allows animals to adjust behavioral responses, potentially affecting survival and reproduction (fitness). These in turn determine demography, and the potential for adjustment to climate change. Photo: Southern pied babbler ( Turdoides bicolor ) in the Kalahari Desert panting and wingspreading to dissipate heat (photo credit: Nicholas B. Pattinson).